Literature, Literary Studies, and Medical Ethics: The Interdisciplinary Question - Montgomery, Kathryn (The Hastings Center report, 2001)
How do we know what is right, or before that, how do we recognize what is morally salient? Such matters lie deeper than can be plumbed by traditional philosophical modes of inquiry alone. Careful study of them requires also the study of literature, with the meticulous appraisal that it encourages of the intricate, tangled issues involved in apprehending the world, finding our way in it, and representing it to others. In this way, the study of literature contributes to a richer and more complex perspective on moral problems, and a more cautious view of the status and breadth of attempts to solve those problems.